História e patrimônio cultural dos ciganos no Rio Grande do Sul: análise dos relatos orais e documentais - Rista, Sandro Estevão (2022)
The present text aims to analyze the memory of the gypsy people through the use of oral and documentary sources, seeking to deepen the historical knowledge about this ethnic group marked by orality. In this sense, the work aims to: understand the use of oral and documentary sources in the process of historical analysis; comment on the origin of the gypsies; perform the analysis of the oral accounts, stories and documents collected from the gypsies. The research was carried out using a bibliographic research methodology, complemented by a field research based on interviews and photo analyses. It was found that although the gypsy people don’t have a culture described in books, they have a rich cultural tradition that has been maintained from generation to generation through oral transmission, which has kept their identity preserved. It was also observed the need to break down certain cultural barriers that do not accept diversity, especially of minorities, and the need to destroy certain stereotypes imposed throughout history that end up stigmatizing certain ethnic groups, such as the gypsies. It is understood that education plays an important role in disseminating knowledge about the gypsies. This will contribute to breaking down the established cultural barriers.